Marine Macroalgae Display Bioreductant Efficacy for Fabricating Metallic Nanoparticles: Intra/Extracellular Mechanism and Potential Biomedical Applications - Sabiha Mahmood Ansari; Quaiser Saquib; Valeria De Matteis; Hend Awad Alwathnani; Sulaiman Ali Alharbi; Abdulaziz Ali Al-Khedhairy (Bioinorganic Chemistry and Applications)
The application of hazardous chemicals during nanoparticle (NP) synthesis has raised alarming concerns pertaining to their biocompatibility and equally to the environmental harmlessness. In the recent decade, nanotechnological research has made a gigantic shift in order to include the natural resources to produce biogenic NPs. Within this approach, researchers have utilized marine resources such as macroalgae and microalgae, land plants, bacteria, fungi, yeast, actinomycetes, and viruses to synthesize NPs. Marine macroalgae (brown, red, and green) are rich in polysaccharides including alginates, fucose-containing sulfated polysaccharides (FCSPs), galactans, agars or carrageenans, semicrystalline cellulose, ulvans, and hemicelluloses. Phytochemicals are abundant in phenols, tannins, alkaloids, terpenoids, and vitamins. However, microorganisms have an abundance of active compounds ranging from sugar molecules, enzymes, canonical membrane proteins, reductase enzymes (NADH and NADPH), membrane proteins to many more. The prime reason for using the aforesaid entities in the metallic NPs synthesis is based on their intrinsic properties to act as bioreductants, having the capability to reduce and cap the metal ions into stabilized NPs. Several green NPs have been verified for their biocompatibility in human cells. Bioactive constituents from the above resources have been found on the green metallic NPs, which has demonstrated their efficacies as prospective antibiotics and anti-cancer agents against a range of human pathogens and cancer cells. Moreover, these NPs can be characterized for the size, shapes, functional groups, surface properties, porosity, hydrodynamic stability, and surface charge using different characterization techniques. The novelty and originality of this review is that we provide recent research compilations on green synthesis of NPs by marine macroalgae and other biological sources (plant, bacteria, fungi, actinomycetes, yeast, and virus). Besides, we elaborated on the detailed intra- and extracellular mechanisms of NPs synthesis by marine macroalgae. The application of green NPs as anti-bacterial, anti-cancer, and popular methods of NPs characterization techniques has also been critically reviewed.